The national literacy program in Brazil and the educational elements in the basic reforms during Joao Goulart's government (1963-1964) - Fidelis, Thiago [UNESP] (Centro Univ La Salle, 2023)
In 1961, after Janio Quadros's resignation as president, the vice president, Joao Goulart, returning from a trip to China, was prevented from taking offi ce by the Army's high command leaders. They were fearful that the politician would implement a communist government in Brazil, in a context of intense disputes promoted by the Cold War. After an agreement involving the consolidation of Parliamentarism, Joao Goulart was allowed to be president, and this system was maintained until 1963, after being revoked by a popular plebiscite. From then on, the government began to better structure the so-called Basic Reforms, which would be actions aimed at restructuring several areas of Brazil, with Agrarian Reform being the most discussed among them. However, Education was also one of the main aspects of these Reforms, and the main action was the creation, in early 1964, of the National Literacy Program, an adaptation of a literacy project implemented in some regions of the Northeast region by professor Paulo Freire, who used to work at Universidade de Recife. In this structured process at the regional level, the method consisted of providing literacy to a large group of adults in just 45 days, using elements such as the language and worldview of these people, combined with a political perspective in teaching, stimulating criticality and struggling for better living conditions for these groups. Thus, the main purpose of this article is to discuss the development of this Program in that political context. Besides, we also provide an overview of its ephemeral duration, since it was extinguished together with the government of Joao Goulart by a coup d 'etat in April 1964.
Keywords: National Literacy Program; Paulo Freire; Joao Goulart